Promoting Women's Access to Economic Opportunities : Montenegro - World Bank Group (World Bank, Washington, DC, 2018)
Prospects for sustainable and faster economic growth and higher living standards in Montenegro rely on increasing employment opportunities for all. By maintaining the current structure of labor participation, Montenegro is not capitalizing on the educated young population, given that less than half (46.9 percent) of women 15-64 years old are actively contributing to the economy through employment. Closing gender gaps in access to economic opportunities requires removing the barriers and disincentives to employment and entrepreneurship for women. These include: (i) improving access to assets and productive inputs, (ii) providing access to child and elder care, and (iii) removing disincentives and barriers embedded in labor taxation and regulation, and (iv) increasing employability of women through effective active labor market policies & adequate skills and training. Cross-cutting policies around social norms and discrimination; access to information; and monitoring and evaluation systems are also important.